(untitled) (Baghdad Science Journal, 2021)
This study was performed on the Tigris River (Baghdad city section) during the period between December 2016 and December 2018 to assess seasonal variation in water quality using the Overall Index of Pollution (OIP). The OIP is one of the reliable tools for the assessment of surface water quality. To calculate OIP-values, eight parameters were measured ( pH, Dissolved Oxygen "DO", Biological Oxygen Demand "BOD", Total Dissolved Solid "TDS", Total Hardness "TH", calcium "Ca", Sulphate "SO4" and Alkalinity). The results showed the anthropogenic activities impact of Baghdad population that directly discharge of "inadequate treated" waste water to the river. OIP values were acceptable (1˃OIP˃ 1.7) in 2011, 2012, 2013 and 2018. However, in 2014 and 2017,the OIP recorded values that were acceptable and tend to be slightly polluted (1.7˃OIP˃2.5). The impairment of water quality during 2014 and 2017 might be caused by the decrease in the water share feeding Tigris River from Turkey due to the construction of many dams. Also, markedly reduced rain precipitation rates were recorded in these periods. The study suggests conducting continuous monitoring programs and establishing a reliable Iraqi classification system for water quality by a specialized scientific panel.